Relationship of Vitamin D Deficiency and Fatty Liver in Children as Defined by Multiple Imaging and Histologic Endpoints. Issue 2 (30th May 2021) - Rudolph, Bryan; Selig, Tyler; Li, Yingjie; Ovchinsky, Nadia; Kogan-Liberman, Debora; Liszewski, Mark C.; Levin, Terry L.; Ewart, Michelle; Liu, Qiang; Viswanathan, Shankar; Lin, Juan; Xue, Xiaonan; et al.
Abstract : Objectives: The relationship between vitamin D deficiency (VDD) and pediatric nonalcoholic fatty liver disease (NAFLD) remains uncertain due to conflicting results and few studies with histologic endpoints. We therefore used multiple imaging and histologic NAFLD endpoints to more comprehensively assess the association between VDD and NAFLD in a large pediatric population. Methods: Data were obtained from an ongoing pediatric NAFLD study in Bronx, NY. Briefly, overweight and obese children aged 2 to 18 years with alanine aminotransferase levels ≥35 U/L were serially enrolled. Liver biopsy was obtained in accordance with clinical guidelines. All participants had liver imaging, namely, controlled attenuation parameter to assess steatosis and, to assess fibrosis, vibration controlled transient elastography (FibroScan), and acoustic radiation force impulse imaging. Levels of 25-hydroxyvitamin D were measured serologically. Results: N = 276 (88%) of 315 participants had 25-OH vitamin D results, of whom 241 (87%) were Hispanic, 199 (72%) were male, and 92 (33%) underwent liver biopsy. VDD was univariately associated with high waist circumference ( P = 0.004), high-density lipoprotein level ( P = 0.01), season ( P = 0.009), and controlled attenuation parameter score ( P = 0.01). In multivariate analysis, only waist circumference ( P = .0002) and biopsy inflammation grade ( P = 0.03) were associated with VDD, though the latter had not approximated statistical significance in univariate analysis ( P = 0.56). There was no association between VDD and hepatic steatosis, ballooning, NAFLD activity score, and acoustic radiation force impulse or vibration controlled transient elastography elasticity scores. Conclusions: VDD was not associated with NAFLD defined by imaging and histologic endpoints, except for a possible relation with histologic inflammation grade.